100 Intimate partner violence victimisation and perpetration prevalence and correlates among men in primary care settings. (19th September 2017) - Singh, Vijay; Buschmann, Bethany; Epstein-Ngo, Quyen; Cunningham, Rebecca
Abstract : Statement of Purpose: Few studies inform primary care-based identification and response to male intimate partner violence (IPV) victimisation or perpetration. The purpose of this study is to determine psychological or physical IPV victimisation and perpetration (1) prevalence among men in family medicine settings, and (2) correlates including demographics, mental health, alcohol and substance use. Methods/Approach: Men aged 18 to 70 were recruited in waiting rooms of two family medicine centres in urban and suburban Midwestern towns. Men completed surveys with measures of past year psychological and physical IPV victimisation and perpetration, alcohol misuse, substance use, mindfulness, and depression. Results: Of 236 men with a partner (average age 36.4 years, 44.6% African-American, 53.4% living with children), 162 (68.6%) and 152 (64.4%) reported psychological or physical IPV victimisation and perpetration, respectively. Poisson regression analyses showed IPV victimisation is positively associated with substance use (IRR 1.49, 95% CI 1.04–2.13) and depression symptoms (IRR 1.17, 95% CI 1.06–1.29), and negatively associated with higher education (IRR 0.73, 95% CI 0.61–0.88). IPV perpetration is positively associated with living with children (IRR 1.60, 95% CI 1.16–2.20), substance use (IRR 1.71, 95% CI 1.20–2.44), and depression symptoms (IRR 1.14, 95% CI 1.03–1.26), and negatively associated with higher education (IRR 0.83, 95% CI 0.69–1.00). Mindfulness was a significant IPV correlate in multivariate models without depression. Conclusions: Nearly 2 in 3 men in family medicine waiting rooms report psychological or physical IPV victimisation or perpetration. Male IPV victimisation and perpetration correlates are similar for education, mindfulness, substance use and depression, though living with children was a risk factor only for IPV perpetration. Limitations include no partner reports. Significance and Contributions to Injury and Violence Prevention Science: The findings help inform prevention and intervention efforts for male IPV, particularly the protective effect of education and mindfulness, and risk factors of substance use, depression symptoms, and living with children.